WHAT IS THE FATE OF TRADE UNIONS IN ITALY? RESULTS OF A TRAINING COURSE ADDRESSED TO THE EXECUTIVE BOARD - Ronsivalle, Gaetano Bruno; Boldi, Arianna (PEOPLE: International Journal of Social Sciences, 2018)
With the rising of technology, occupations will have to face growth, reduction or redesign: therefore, changes in organizations, human capital and processes involving people will occur. We focus on the main Trade Union operating in Italy. At first, we present an analysis of this organization. Then, we describe a training course addressed to a sample of Trade Union Executive Board. Finally, we provide suggestions about some possible development scenarios. As a result, we may underline three critical issues: a) People minimize the potential effects of automation on jobs and on their own career and they are not prepared to this change; 2) The organization is losing its bargaining power and risks to disappear, leaving a gap in the intermediary function between the employer and the employees; 3) The Executive Board fails in making forecasts and strategic planning, to effectively negotiate with the employer. The main output of the course is a Project Work which contains a description of a strategic intervention which could be implemented in the organization to effectively deal with the future changes.